2017
DOI: 10.1111/1744-9987.12586
|View full text |Cite
|
Sign up to set email alerts
|

Hemodialysis Decreases the Concentration of Accumulated Plant Phenols in the Plasma of Patients on Maintenance Dialysis: Influence of Residual Renal Function

Abstract: Plant phenols may accumulate in end-stage kidney disease. The effect of hemodialysis on their plasma concentration remains poorly determined. Contingent on concentration, health-promoting or noxious effects occur; therefore, we assessed plasma concentration in hemodialyzed patients. In total, 21 maintenance hemodialyzed patients with diuresis < 500 mL per day (with oliguria), nine hemodialyzed patients with diuresis ≥ 500 mL per day (without oliguria) and 31 healthy volunteers were included. Nine phenolic acid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 43 publications
0
10
0
Order By: Relevance
“…Also, consumption of pomegranate before dialysis session may reduce its beneficial effect since pomegranate polyphenols pass through the dialysis membrane and are discarded in the dialysate. 36,37 Similarly, the lack of PJ effect on the total and LDL cholesterol in our study may be partly due to relatively normal levels of these lipids in the participants as other studies on diabetes patients with elevated blood lipids showed promising results. 38,39 The lipid-lowering and anti-atherogenic properties of pomegranate may be attributed to a number of mechanisms such as regulating the expression of the genes involved in lipogenesis and fatty acid oxidation in the liver 40 ; increasing the expression and activity of paraoxonase-1; the antioxidant enzyme in HDL particles which prevents LDL oxidation 41 ; and suppression of oxidized LDL degradation and of cholesterol synthesis in macrophages.…”
Section: Discussionmentioning
confidence: 53%
See 1 more Smart Citation
“…Also, consumption of pomegranate before dialysis session may reduce its beneficial effect since pomegranate polyphenols pass through the dialysis membrane and are discarded in the dialysate. 36,37 Similarly, the lack of PJ effect on the total and LDL cholesterol in our study may be partly due to relatively normal levels of these lipids in the participants as other studies on diabetes patients with elevated blood lipids showed promising results. 38,39 The lipid-lowering and anti-atherogenic properties of pomegranate may be attributed to a number of mechanisms such as regulating the expression of the genes involved in lipogenesis and fatty acid oxidation in the liver 40 ; increasing the expression and activity of paraoxonase-1; the antioxidant enzyme in HDL particles which prevents LDL oxidation 41 ; and suppression of oxidized LDL degradation and of cholesterol synthesis in macrophages.…”
Section: Discussionmentioning
confidence: 53%
“…Some of the controversy over the results of different studies may be explained by the baseline values of triglycerides and HDL cholesterol which probably should be at unfavorable levels in order for pomegranate to exert its benefit. Also, consumption of pomegranate before dialysis session may reduce its beneficial effect since pomegranate polyphenols pass through the dialysis membrane and are discarded in the dialysate . Similarly, the lack of PJ effect on the total and LDL cholesterol in our study may be partly due to relatively normal levels of these lipids in the participants as other studies on diabetes patients with elevated blood lipids showed promising results .…”
Section: Discussionmentioning
confidence: 59%
“…In vitro work has shown that phenylacetic acid increases ROS formation (227), impairs mitochondrial metabolism (228), and can directly inhibit renal tubular efflux pumps (229). Another microbial pathway for phenylalanine leads to the production of mtyramine, which undergoes further enzymatic conversion to 3-hydroxyphenylacetic acid (230), which is elevated in the plasma of hemodialysis patients (231). Presence of phenylacetic acid in plasma is dependent on the gut microbiota (156) and rats with adenine-induced CKD receiving an RSsupplemented diet had reductions in the concentration of 3hydroxyphenylacetic acid by 71% in cecal digesta and 64% in the serum (103), suggesting that targeting of the gut microbiota may prove a useful therapy.…”
Section: Phenylalanine Metabolitesmentioning
confidence: 99%
“…Some of the controversy over the results of different studies may be explained by baseline values of triglycerides and HDL cholesterol in participants which likely need to be in unfavorable levels in order for pomegranate to exert its benefit. Also, consumption of pomegranate before dialysis session may reduce its beneficial effect because pomegranate polyphenols pass through dialysis membrane and are discarded in the dialysate [32,33].…”
Section: Discussionmentioning
confidence: 99%